TERAPI STIMULASI KOGNITIF UNTUK LANSIA DENGAN MILD COGNITIVE IMPAIRMENT: STUDI EKSPERIMENTAL DI PANTI WREDA - Nathalie Sanchia; Magdalena Surjaningsih Halim (PERDOSNI, 2019)
COGNITIVE STIMULATION THERAPY FOR ELDERLY WITH MILD COGNITIVE IMPAIRMENT: AN EXPERIMENTAL STUDY IN NURSING HOMEABSTRACTIntroduction: Mild cognitive impairment (MCI) is a transitional stage between the elderly’s normal (expected) cognitive decline and the more serious decline caused by dementia that needs interventions. One of the non-pharmacological interventions that can be done is cognitive stimulation therapy (CST). Research has shown that CST can stabilize and/ improve cognitive function in the elderly with MCI.Aims: To find out the differences in cognitive functions in the elderly with MCI and given CST intervention and elderly with MCI not given CST intervention.Methods: This was an experimental study that included elderly aged 60 years old divided into experimental and control group, each consists of four subjects. The experimental group was given CST twice a week with a total of fifteen meetings, but not on the control group. All subjects were subjected to cognitive examinations using neuropsychological instruments before, after, and one month after CST was completed. The statistical analysis performed in this study was Mann-Whitney U Test.Results: There was a significant difference in cognitive function in the attention domain with the trail making test sub-test and the memory domain with the digit pan sub-test after the CST is finished. One month after CST is completed, there were significant differences in cognitive function, in the memory domain.Discussion: The elderly group with MCI given CST has a different cognitive function than elderly group who are not given CST.Keywords: Cognitive function, elderly, mild cognitive impairment, nursing houseABSTRAKPendahuluan: Gangguan kognitif ringan atau mild cognitive impairment (MCI) merupakan proses transisi antara penurunan kognitif normal dan demensia yang perlu diintervensi. Salah satu intervensi non-farmakologis yang dapat dilakukan adalah cognitive stimulation therapy (CST). Banyak penelitian menunjukkan bahwa CST dapat menstabilkan dan/meningkatkan fungsi kognitif pada lansia dengan MCI.Tujuan: Untuk mengetahui pengaruh intervensi CST terhadap fungsi kognitif lansia dengan MCI.Metode: Studi eksperimental pada subjek lansia usia 60 tahun yang dibagi menjadi kelompok eksperimen dan kontrol yang masing-masing terdiri dari 4 subjek. Kelompok eksperimen dilakukan CST dua kali seminggu sebanyak lima belas kali pertemuan, tidak pada kelompok kontrol. Seluruh subjek dilakukan pemeriksaan kognitif dengan menggunakan instrumen neuropsikologi sebelum, sesudah, dan satu bulan setelah CST selesai. Analisis statistik menggunakan Mann- Whitney U test.Hasil: Terdapat perbedaan fungsi kognitif yang signifikan pada domain atensi dengan subtes Trail Making Test dan domain memori dengan subtes digit span setelah CST selesai. Satu bulan setelah CST selesai, terdapat perbedaan fungsi kognitif yang signifikan pada domain memori.Diskusi: Kelompok lansia dengan MCI yang diberikan CST memiliki fungsi kognitif yang berbeda dengan kelompok lansia yang tidak diberikan CST.Kata kunci: Fungsi kognitif, gangguan kognitif ringan, lansia, panti wreda